Future of Archives: The Impact of Computerization on Archival Development in Vietnam and Experiences from Germany - Phong, Vu Dinh; Justus Liebig University Giessen (My University, 2026)
This study, “Future of Archives: The Impact of Computerization on Archival Development in Vietnam and Experiences from Germany,” is an empirical investigation that examines how computerization reshapes archival development in Vietnam and Germany. It traces the field’s shift from traditional to digital archives, clarifying the opportunities and risks that arise along the way. Rather than treating computerization as a purely technological shift, the study conceptualizes it as a socio-institutional transformation that redefines archival authority, lifecycle management, and public access. In Vietnam, the research focused on the activities of the four National Archives Centers, namely Centers I, II, III, and the National Archives Center for Digital and Preventive Records, as well as selected provincial and local historical archives. The author conducted a six-month internship at the National Archives Center III to observe digital operations and professional practices. In Germany, the Hessian State Archives (Hessisches Landesarchiv, HLA) serves as the primary case study, representing a mature, standardized, and legally integrated model of digital archiving. Methodologically, the study adopted a comparative case-study methodology, combining qualitative and documentary approaches. Data were collected through 24 semi-structured interviews with archivists, policymakers, IT experts, and institutional leaders, complemented by an analysis of relevant primary and secondary sources. This empirical design provided a comprehensive understanding of archival development in both countries, revealing how legal frameworks, institutional arrangements, professional capacities, technological infrastructures, and user-oriented factors interact to shape their trajectories toward digital transformation. Building on the Socio-Technical systems theory, Institutional Theory and Isomorphism, and Innovation Diffusion and Technology Acceptance Model frameworks (Chapter II), the study conceptualizes computerization not merely as a technological shift but as a socio-institutional process that redefines archival practices, professional competencies, and user engagement. The analysis (Chapters V, VI, and VII) reveals that HLA represents a coherent and OAIS-conformant digital ecosystem that integrates DIMAG for preservation and Arcinsys for access. In Vietnam, digital transformation has accelerated significantly in recent years, particularly with the adoption of the 2024 Archives Law and related implementing regulations. This normative modernization represents a major institutional milestone. However, implementation remains uneven across administrative levels. While the legal framework provides a comprehensive foundation, operational standardization, interoperability, hybrid professional capacity, and preservation infrastructure consolidation require further strengthening. The key divergence between the two countries, therefore, lies not in legal recognition of digital archives but in the degree of governance consolidation and operational coherence. In both contexts, the digital transformation of archives reflects multiple interconnected developments: (1) digitization of analog materials; (2) online discovery and metadata dissemination; (3) remote access to digital surrogates; (4) governance of born-digital records; and (5) adoption of emerging technologies such as AI and digital platforms (Chapter IX). These advances improve accessibility and automation, but heighten risks related to authenticity, privacy, cybersecurity, sustainability, and ethics, requiring continuous investment and governance innovation (Chapter X). This dissertation approaches the future of archives not as a fixed or prescriptive concept; however, within this field, the study identifies the hybrid archives as a context-specific model of archival future, one that reflects the co-existence of analog and digital logics, the interaction of technology and institution, and the balance between continuity and innovation (Chapter VIII). Policy recommendations emphasize (i) legal reform and standards for transfer/metadata; (ii) trusted digital repositories and OAIS-aligned preservation; (iii) workforce transformation toward hybrid competencies; (iv) user-centered services and open access; and (v) cybersecurity and ethical frameworks (Chapter VII, Chapter X). The comparative analysis suggests that experiences from German archives, particularly the HLA, provide valuable and transferable insights for informing the future development of archival institutions in Vietnam. Despite its specific focus on Vietnam and Germany, the study also contributes to broader discussions concerning the integration of digital technologies into archival systems and the institutional adaptation of archives in the digital age.
Keywords: Archives; Digital Transformation; Archival Development; Computerization; Vietnam; Germany; ddc:020; ddc:900; ddc:930